Associations Between Perception of Parental Behavior and “Person Picking an Apple From a Tree” Drawings Among Children With and Without Special Educational Needs (SEN) - Bat Or, Michal; Papadaki, Andriani; Shalev, Or; Kourkoutas, Elias (Frontiers in Psychology, 2018)
The present study examines and compares associations between perceptions of parental acceptance/rejection in 191 Greek school age children (84 inclusion class students and 107 typical class students, age range 10-12), and their “Person Picking an Apple from a Tree” (PPAT) drawings. Perception of parental behavior was measured by the "Parental Acceptance-Rejection Questionnaire” (Rohner & Khaleque, 2005). Drawing content was analyzed quantitatively according to a reliable rating system called the Symbolic Content in PPAT drawings (SC-PPAT: Bat Or, Ishai, & Levi, 2014, 2016). We employed k-means cluster analysis and obtained three relatively discrete PPAT scripts. Drawing content elements and scripts were found to be associated with children’s perceptions of parental behavior; these associations were found mainly among children with special educational needs (SEN) and boys. Results are discussed in terms of children’s subjective experience, clinical implications, and future research directions.